2022
DOI: 10.1186/s12889-022-12828-3
|View full text |Cite
|
Sign up to set email alerts
|

The design and impact of culturally-safe community-based physical activity promotion for immigrant women: descriptive review

Abstract: Background Immigrant women have low rates of physical activity (PA), placing them at risk for chronic diseases. Some research suggests that strategies targeting this group must be culturally-safe and community-based. This study aimed to identify the design (i.e. characteristics) and impact of culturally-safe community-based PA promotion for immigrant women. Methods We conducted a descriptive review by searching MEDLINE, EMBASE, SPORTDiscus, CINAHL,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 63 publications
(91 reference statements)
0
5
0
Order By: Relevance
“…Ethnic minorities, particularly elderly women, are more affected by this, while the cultural emphasis on family in Latino communities encourages intergenerational PA participation [ 32 ]. A descriptive review [ 74 ], also noted the low participation of ethnic minority older women in PA and the need to identify culturally safe community-based PA. Additionally, language is a factor that needs to be considered. Organizing intergenerational sports activities in the participants' primary language can enhance their sense of self-efficacy in participating in these activities.…”
Section: Discussionmentioning
confidence: 99%
“…Ethnic minorities, particularly elderly women, are more affected by this, while the cultural emphasis on family in Latino communities encourages intergenerational PA participation [ 32 ]. A descriptive review [ 74 ], also noted the low participation of ethnic minority older women in PA and the need to identify culturally safe community-based PA. Additionally, language is a factor that needs to be considered. Organizing intergenerational sports activities in the participants' primary language can enhance their sense of self-efficacy in participating in these activities.…”
Section: Discussionmentioning
confidence: 99%
“…These findings complement those from Piedra et al (2018) and the ¡Caminemos! Program as well as the conceptual framework for culturally-safe physical activity (Gagliardi et al, 2022) in that culturally relevant and age-appropriate programming is critical. Our results are also consistent with a recently published systematic review highlighting the essential nature of tailoring physical activity interventions for culturally and linguistically diverse populations in the U.S.…”
Section: Discussionmentioning
confidence: 99%
“…The authors noted that cultural adaptations may be necessary based on consultation with the community, such as adjusting to the common language spoken by participants, ensuring cultural and linguistic concordance of program personnel with participants, and providing culturally relevant intervention materials and content (El Masri et al, 2022). Physical activity programs should aim to acknowledge and integrate factors that may affect participation such as cultural values, language preferences, social norms, and cultural concordance of program facilitators (Gagliardi et al, 2022; Joseph et al, 2017; Marquez et al, 2020). Previous research has demonstrated that a culturally tailored aerobic dance program (e.g., using bilingual community staff to implement all aspects of the study in Spanish, adapting for lower formal education levels, and addressing cultural myths) increased physical activity among Latinas facing cultural, social, and environmental barriers to routine physical activity (Hovell et al, 2008).…”
Section: Discussionmentioning
confidence: 99%
“…It is necessary to follow-up for a longer period in the future and conduct a study to deliver interventions to various married immigrants using CHWs. In addition, since there are cases of using CHWs in other health promotion areas such as diabetes management [ 38 ] and physical activity promotion [ 39 ], we propose a study that provides interventions for immigrants living in Korea.…”
Section: Discussionmentioning
confidence: 99%